2017
DOI: 10.1016/j.neuroscience.2016.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ibuprofen on cognition and NMDA receptor subunit expression across aging

Abstract: Age-related declines in long- and short-term memory show relationships to decreases in N-methyl-D-aspartate (NMDA) receptor expression, which may involve inflammation. This study was designed to determine effects of an anti-inflammatory drug, ibuprofen, on cognitive function and NMDA receptor expression across aging. Male C57BL/6 mice (ages 5, 14, 20, and 26 months) were fed ibuprofen (375 ppm) in NIH31 diet or diet alone for 6 weeks prior to testing. Behavioral testing using the Morris water maze showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…In contrast to GluN2A, expression of GluN2B protein [6264, 67, 68, 78, 83, 84] and GluN2B mRNA [60, 7678, 83, 85] is generally reported to decline in the hippocampus with advanced age. One problem is that few studies have examined the expression of both subunits in the same animal.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to GluN2A, expression of GluN2B protein [6264, 67, 68, 78, 83, 84] and GluN2B mRNA [60, 7678, 83, 85] is generally reported to decline in the hippocampus with advanced age. One problem is that few studies have examined the expression of both subunits in the same animal.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, non-steroidal anti-inflammatory drugs (NSAIDs) can ameliorate age-related cognitive deficits and impaired NMDA receptor-dependent synaptic plasticity (Casolini, et al, 2002,Jain, et al, 2002,Marquez Loza, et al, 2017,McGuiness, et al, 2017,Melnikova, et al, 2006,Mesches, et al, 2004,Small, et al, 2008). However, whether NSAIDs act on the redox-mediated NMDA receptor hypofunction is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence has indicated that aging is associated with hypofunction of NMDARs in regions of the brain associated with synaptic plasticity, memory, and learning ( Kumar, 2015 ). For instance, NMDAR-mediated excitatory postsynaptic potentials (EPSPs) in the hippocampus are decreased in aged rodents ( Yang et al, 2010 ; Haxaire et al, 2012 ) and reduced protein expression of NMDARs is observed in the hippocampus of aged animals ( Liu et al, 2008 ; Zhao et al, 2009 ; Marquez Loza et al, 2017 ). Nowadays, it is generally accepted that hypofunction of NMDARs contributes to impediments in memory and learning that occur with increased age ( Das and Magnusson, 2011 ; Foster, 2012 ; Kumar and Foster, 2013 ; Li et al, 2017 ) and augmenting the expression and functional activity of the NMDAR subunit could overcome the cognitive impairments in aged animals ( Slutsky et al, 2010 ; Robillard et al, 2011 ; Brim et al, 2013 ; Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%